Deposition and Characterization of Molybdenum Thin Film Using Direct Current Magnetron and Atomic Force Microscopy - Muhtade Mustafa Aqil; Mohd Asyadi Azam; Mohd Faizal Aziz; Rhonira Latif (Journal of Nanotechnology)
In this paper, pure molybdenum (Mo) thin film has been deposited on blank Si substrate by DC magnetron sputtering technique. The deposition condition for all samples has not been changed except for the deposition time in order to study the influence of time on the thickness and surface morphology of molybdenum thin film. The surface profiler has been used to measure the surface thickness. Atomic force microscopy technique was employed to investigate the roughness and grain structure of Mo thin film. The thickness and grain of molybdenum thin film layer has been found to increase with respect to time, while the surface roughness decreases. The average roughness, root mean square roughness, surface skewness, and surface kurtosis parameters are used to analyze the surface morphology of Mo thin film. Smooth surface has been observed. From grain analysis, a uniform grain distribution along the surface has been found. The obtained results allowed us to decide the optimal time to deposit molybdenum thin film layer of 20–100 nm thickness and subsequently patterned as electrodes (source/drain) in carbon nanotube-channel transistor.